Características de crecimiento del pasto Cuba OM-22 (Pennisetum purpureum x Pennisetum glaucum) en condiciones edafoclimáticas de la estación experimental “el Padmi” de la Universidad Nacional de Loja - Jara Silva, Rachel Sarahi (2023)
The present investigation was carried out with the purpose of evaluating the agronomic characteristics of the Cuba OM-22 grass (Pennisetum purpureum x pennisetum glaucum) under edaphoclimatic conditions of the experimental station "El Padmi" of the National University of Loja. For this purpose, in a previously established Cuba OM-22 grass crop, an equalization cut was made and data on the variables under study were collected and recorded at 30, 60 and 120 days. The following variables were evaluated: plant height, number of leaves, number of stems, leaf weight, stem weight, leaf/stem ratio, green forage production, dry matter content, and dry matter production. The data were processed and subjected to an analysis of variance using a completely randomized design (DCA) and Tukey's test (<0.05). The results showed a statistical difference (P<0.0001) between the cutting ages for all the variables, with values greater than 120 cutting days, obtaining a height of 1.30 meters, 141 leaves/plant, 19 stems/plant, 585 grams of leaves, 457 grams of stems, 62.52 t/ha/cut of green forage, 14.19 t/ha/cut of dry forage and 22.7% dry matter. Concluding that the Cuba OM 22 grass reaches maturity after 60 days, since there is a balance in the productive and nutritional part. It is recommended to implement the culture of Cuba OM-22 as a forage bank to complement the feeding of cattle. Keywords: cutting age, growth, forage production, bovine feeding.